Ovomucoid Specific Immunoglobulin E as a Predictor of Tolerance to Cooked Egg. Issue 3 (September 2015) - Bartnikas, Lisa M.; Sheehan, William J.; Tuttle, Katherine L.; Petty, Carter R.; Schneider, Lynda C.; Phipatanakul, Wanda
Background: Ovomucoid is the dominant allergen in hen's egg. Although several studies evaluated the utility of ovomucoid specific immunoglobulin E (sIgE) levels in predicting baked (e.g., muffin or cupcake) or raw egg food challenge outcomes, studies that evaluated ovomucoid sIgE as a predictor of cooked egg (e.g., scrambled or hard boiled) challenge outcomes are limited. Objective: To determine the relation of ovomucoid sIgE levels with cooked egg food challenge outcomes. Methods: A retrospective review of 44 children who underwent cooked egg food challenge and who had the ovomucoid sIgE level measured. Results: Thirty-six of 44 children (81.8%) passed cooked egg challenge. The ovomucoid sIgE level predicted cooked egg challenge outcome (passed median, <0.35 kU/L [range, <0.35–0.64 kU/L]; failed median, 0.40 kU/L [range, <0.35–3.13 kU/L]; p = 0.004). Ovomucoid sIgE levels correlated with egg white (EW) sIgE levels (Spearman correlation coefficient, 0.588; p = 0.001). Receiver operating characteristic curve analysis of ovomucoid and EW sIgE demonstrated areas under the curve of 0.711 and 0.766, respectively. No significant difference was observed among those immunologic parameters in their abilities to predict cooked egg challenge outcome (p = 0.559). Conclusion: The ovomucoid sIgE level may be helpful in predicting cooked egg challenge outcomes. However, our study did not support a role for ovomucoid sIgE replacing EW sIgE testing in evaluating egg allergy.